Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Non-linear PCM bitstreams according to the ATRAC, ATRAC2/3 and ATRAC-X formats Part 7, (31st October 2016) - British Standards Institution,
No abstract available